Structural and temporal evolution of a reactivated brittle-ductile fault - Part II: Timing of fault initiation and reactivation by K-Ar dating of synkinematic illite/muscovite - Torgersen, E.; Viola, G.; Zwingmann, Horst; Harris, C. (Elsevier BV, 2014)
Present-day exposures of ancient faults represent only the end result of the faults' often protracted and heterogeneous histories. Here we apply K–Ar dating of synkinematic illite/muscovite to constrain the timing of the complete temporal evolution of a complex, multiply-reactivated brittle–ductile fault, the Kvenklubben Fault in northern Norway. All obtained ages vary as a function of grain size. Geologically significant events are identified principally on the basis of detailed structural analysis presented in a companion paper (Torgersen and Viola, 2014). Faulting initiated at View the MathML source531±11Ma, but most strain was accommodated during Caledonian compression at View the MathML source445±9Ma. The fault was reactivated extensionally at View the MathML source121±5Ma. C and O isotopic composition of carbonates and silicates in the fault rocks demonstrates that mineral authigenesis was linked to wall–rock disintegration through dolomite decarbonation and metabasalt carbonation. We suggest that the commonly observed case of age decreasing with grain size in K–Ar and 40Ar/39Ar dating of brittle fault rocks can be interpreted as a consequence of mixing between two end-member illite/muscovite generations: an authigenic and a protolithic, in which the finest authigenic grains constrain the timing of the last faulting increment. Integrating detailed structural analysis with age dating is the key towards a better understanding of fault architecture development and the temporal evolution of strain localization and deformation mechanisms.